Chronic Diarrhea Due to Intestinal Amyloidosis - Lydia D Simatupang; Kharia Utia; Ari Fahrial Syam; Marcellus Simadibrata; Arya Govinda; Ening Krisnuhoni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Amyloidosis is a rare disease, when diagnosed it’s incurable and mostly affect over 40 years old male. Diagnostic is confirmed if histopathologic stained positive with Congo red and evidence of monoclonal protein. Survivals for untreated patients are 13 months in primary amyloidosis but if secondary to other chronic disease and systemic, survival could be 3-4 years. It can not be prevented but when affected, control of the underlying illness can prevent progression of amyloidosis. We report a rare case of a 67 year old male, who came with chronic diarrhea. The stool analysis, there were no negative gram microorganisme found, only food maldigestion and fungus infection. Stool analyze from parasitology department were found microspore, but the stool culture were sterile. The patient underwent colonoscopy which revealed hyperemis mucosa in rectum, sigmoid, descending transverse colon. From the biopsy was concluded intestinal amyloidosis. We treated the patient symptomatically and couldn’t find the underlying inflammatory disease which causes the problem. Keywords:  secondary  amyloidosis,  chronic  diarrhea, malabsorption,  colonoscopy,  protein electrophoresis